Reduced butyrylcholinesterase activity is an early indicator of trauma-induced acute systemic inflammatory response - Zivkovic AR; Bender J; Brenner T; Hofer S; Schmidt K (Dove Medical Press, 2016)
Aleksandar R Zivkovic, Jochen Bender, Thorsten Brenner, Stefan Hofer,* Karsten Schmidt* Department of Anesthesiology, Heidelberg University Hospital, Heidelberg, Germany *These authors contributed equally to this work Purpose: Early diagnosis of systemic inflammatory response syndrome is fundamentally important for an effective and a goal-directed therapy. Various inflammation biomarkers have been used in clinical and experimental practice. However, a definitive diagnostic tool for an early detection of systemic inflammation remains to be identified. Acetylcholine (Ach) has been shown to play an important role in the inflammatory response. Serum cholinesterase (butyrylcholinesterase [BChE]) is the major Ach hydrolyzing enzyme in blood. The role of this enzyme during inflammation has not yet been fully understood. This study tests whether a reduction in the BChE activity could indicate the onset of the systemic inflammatory response upon traumatic injury. Patients and methods: This observational study measured BChE activity in patients with traumatic injury admitted to the emergency room by using point-of-care-test system (POCT). In addition, the levels of routine inflammation biomarkers during the initial treatment period were measured. Injury Severity Score was used to assess the trauma severity. Results: Altered BChE activity was correlated with trauma severity, resulting in systemic inflammation. Reduction in the BChE activity was detected significantly earlier compared to those of routinely measured inflammatory biomarkers. Conclusion: This study suggests that the BChE activity reduction might serve as an early indicator of acute systemic inflammation. Furthermore, BChE activity, measured using a POCT system, might play an important role in the early diagnosis of the trauma-induced systemic inflammation. Keywords: trauma, injury, early diagnostics, cholinergic, pseudocholinesterase, SIRS